Primary health care nurses' knowledge, self-efficacy and performance of diabetes self-management support - Zandile K. Landu; Talitha Crowley (AOSIS, 2023)
Background: Patients living with diabetes are primarily managed and supported by nurses in primary health care (PHC). Therefore, PHC nurses require knowledge of diabetes and confidence (self-efficacy) to perform diabetes self-management support (SMS). Aim: This study evaluated the diabetes knowledge, self-efficacy and performance of diabetes SMS by PHC nurses. Setting: Primary health care facilities in King Sabata Dalindyebo subdistrict, O.R. Tambo district, Eastern Cape. Methods: A quantitative cross-sectional and simple correlational design was used. Registered nurses (n = 100) completed a validated self-reporting questionnaire to measure diabetes knowledge, self-efficacy and performance of SMS. Results: Participants' diabetes knowledge mean scores were high (mean of 11.9, standard deviation [s.d.] 1.8, out of 14). Self-efficacy scores (mean 18.91, s.d. 3.2 out of 24) were higher than performance of SMS scores (mean 17.81, s.d. 3.3 out of 24). Knowledge was not associated with self-efficacy or performance, but self-efficacy was positively correlated with performance of SMS (r = 0.78, p 0.01). Nurses with a postgraduate qualification in primary care nursing had significantly higher diabetes knowledge scores (mean = 92.9 vs. 83.8; p = 0.03), and years of experience as a nurse were positively correlated with the performance of SMS (r = 0.21, p = 0.05). Conclusion: Diabetes knowledge of PHC nurses in this study does not translate into self-efficacy and the performance of SMS in practice, indicating the need for specific SMS training, support by experienced mentors, appropriate guidelines and comprehensive integrated chronic care systems. Contribution: This is the first study to report on the SMS self-efficacy and performance of PHC nurses in South Africa.